EFFECT OF FERMENTATION TIME ON MINERAL PROFILE AND TOTAL MOLD OF COWPEA (Vigna unguiculata) TEMPEH - Rahmawati, Irma Sarita; Dyanti, Ghina Putri; Madani, Muhammad Surya; Widyanto, Rahma Micho; Istifani, Lola Ayu; Maulidiana, Annisa Rizky; Aisyiyah, Ekkel Lintang (Jurnal Pangan dan Agroindustri, 2023)
Tempe is one of the popular foods in Indonesia which comes from fermented soybeans with the help of Rhizopus oligosporus. The development of tempeh with non-soy ingredients is starting to be carried out frequently. Cowpea (Vigna unguiculata subsp. unguiculata) is one of the nuts that is often consumed by Indonesian people. Cowpeas can be an alternative substrate for tempeh fermentation, because of their nutritional content, including vitamins and minerals, which are quite good for the body. However, some of these minerals are still bound to the phytic acid compound so it needs to be explained by the fermentation process. This research aimed to determine the ash content, mineral content of iron, calcium, and total mold in cowpea tempeh at a fermentation time of 35, 45, and 54 hours using standard methods. The research design used was a Completely Randomized Design (CRD) with repetition 3 times for each treatment for fermentation duration P1 (35 hours), P2 (45 hours), and P3 (54 hours). The ash and calcium content of cowpea tempeh decreased with fermentation times of 45 and 54 hours compared to 35 hours. In terms of iron content, the amount was almost the same at all fermentation times. Meanwhile, the total number of molds increased with fermentation times of 45 and 54 hours. Based on the results of observations for further research, the fermentation time for making cowpea tempeh used in this optimization was determined to be 35 hours. A fermentation time of 35 hours produces good cowpea tempeh, high calcium content, and efficient time and energy.